Arsitektural Masjid KH. Ahmad Dahlan Gresik - Ela Fatmawati (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: This article discussed the history of the KH Ahmad Dahlan Mosque, Gresik. It used a historical research method which consists of heuristics, verification, interpretation and historiography stages. In approaching the issue, it was assisted by the theory of roles proposed by Bruce J. Biddle and Edwin J. Thomat. The results indicate that KH Ahmad Dahlan Mosque was built in addition to being a place of worship as well as a place of vocation for travelers (serving travelers). The mosque adopts architectural buildings from the Spanish city, and has cultural values both local and non-local in its architectural buildings. The mosque plays several roles in which its main role is still to worship God. Keywords: Architecture, History, and Social Role